Sistemas Hamiltonianos vinculados e redução dimensional em teoria clássica de campos - Santos, Rafael Robson Lino dos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In this work, we introduce the reader to two subjects in field theory: Constrained Hamiltonian Systems and Kaluza-Klein Dimensional Reduction. In the first part of the work, after a brief review of Lagrangian and Hamiltonian formalism, we investigate important properties of Constrained Hamiltonian Systems through the Dirac-Bergmann algorithm, which allows us to analyze these systems correctly. Then, we apply this formalism to five models in the context of field theory, namely, Maxwell, Maxwell- Proca (MP), (linearized) Einstein-Hilbert (EH), Fierz-Pauli (FP), and WTDiff. In the second part, we perform Kaluza-Klein dimensional reductions in order to obtain massive models in D dimensions from their massless correspondents in D + 1 dimensions. Within this approach, we have obtained MP from Maxwell, FP from EH and WTDiffm from WTDiff

Neste trabalho introduzimos o leitor a dois assuntos em teoria de campos: Sistemas Hamiltonianos Vinculados (SHV) e Redução Dimensional a la Kaluza-Klein (KK). Na primeira parte do trabalho, após um breve resumo dos formalismos lagrangiano e hamiltoniano, investigamos importantes propriedades dos SHV através do algoritmo de Dirac-Bergmann, que nos permite analisar estes sistemas de maneira correta. Em seguida, aplicamos esta técnica em cinco modelos de teoria de campos: Maxwell, Maxwell-Proca (MP), Einstein-Hilbert (EH) linearizado, Fierz-Pauli (FP) e WTDiff. Na segunda parte, realizamos reduções dimensionais KK com o intuito de obter modelos massivos em D dimensões a partir do modelo não massivo correspondente em D + 1 dimensões. Com esta abordagem, obtivemos MP a partir de Maxwell, FP de EH e WTDiffm de WTDiff
Bound Hamiltonian systems and dimensional reduction in classical field theory
Keywords: Sistemas hamiltonianos; Teoria de campos (Física); Algoritmos; Hamiltonian systems